An Islamic Economic Law Analysis of the Mudharabah Muqayyadah Contract at Toko Madura Riska in Jakarta - Siti Maisun; Mohammad Mahmudi (Indonesian Journal Economic Review (IJER), 2026)
This study examines the implementation of the mudharabah muqayyadah contract at Toko Madura Riska in Jakarta from the perspective of Islamic Economic Law. The research aims to analyze the practice of the contract and assess its compliance with Sharia principles. This study employed a qualitative method with an empirical juridical approach. Data were collected through interviews, observations, and documentation involving the capital owner and the business manager. The findings show that the partnership is conducted between a capital owner and a business manager with a capital investment of IDR 85,000,000. Profits are shared equally (50:50) and distributed monthly. The practice has fulfilled several essential elements of a mudharabah muqayyadah contract, including the existence of contracting parties, clear capital, and an agreed profit-sharing ratio. However, the contract is conducted orally without written documentation, and business losses are borne by the manager regardless of negligence. These practices are not fully consistent with the principles of Islamic Economic Law. Therefore, the implementation of the mudharabah muqayyadah contract at Toko Madura Riska can be categorized as partially compliant with Sharia principles and requires greater contractual clarity and transparency.